Determination of oxidized titanium, cadmium and copper amount under alternating current electrolysis; Zavodskaya Laboratoriya. Diagnostika Materialov; Vol. 71, № 6 - Korobochkin V. V. Valery Vasilievich (2005, 2005)
The method of the quantitative determination of oxidized under alternating current electrolysis (corrosion) metal, based on measuring of the volumetric content of the allocated hydrogen is designed. The plan of equipment, the operation procedure and the kinetic curves of corrosion received for various metals are given.